Propuesta para Capacitación en Tecnologías Web: Paso Fundamental para Implementar Programas de Educación Virtual - Espinel Ortega, Álvaro; Pérez Castillo, José Nelsón; Angulo Chavarro, Jaime Humberto (Ingeniería, 2001)
The present article considers the importance of the process of qualification of professors in technologies of the infor mation and the communication, oriented to produce content for programs of Virtual Education in Internet or to be used in an Intranet with the purpose of fortifying the actual education or to advance programs of remote education in virtual modality. We talked about in the present I articulate to Technologies WEB, like the set of technologies usedin the processing of information and systems of communications that allow to the production and distribution of contents to advance programs of virtual education using the infrastructure of Internet or intranets. Those technologies are included all to produce multimedia and hypermedia between which we can mention mark languages systems of compression and codification of video, photographs, audio, tools foranimation production, virtual reality, as well as the used communication protocols in model TCP/IP. This article comprises of the results of the developing investigation made of the Thesis of Masters titled Methodologic Considerations for the Implementation of the Specialization in Teleinformática in Virtual Modality in the Francisco Jose de Caldas Distrital University